Design of pick and place and color sorting system using VDI 2221. Issue 1 (December 2020) - Michael, Vinsensius; Halim, Agus; Purna Irawan, Agustinus
Abstract: In order to satistfy people's needs in Industrial era 4.0, many varieties of industrial system design have been developed especially in mechanical and automation sector. One of the examples is the pick and place system. This design aims to show the use and workings from combination of pick and place system and color sorting system. Pick and place system used is a single axis robot with two degrees of freedom and aluminium profile frame. Arduino and TCS230 sensor is used in the system. Design method uses VDI 2221 frame. The chosen design result is variant (5) with a total weighting of VDI value is 7.3175. The calculation in the design is maximum deflection calculation that occurs in the aluminium profile frame which is equal to 3.1263 x 10 -18 m. The pick and place system on the x axis uses a single axis robot type KK60 lead 10 mm which is able to lift 1 kg loads and move at a maximum speed of 790 mm/s as far as 220 mm, while on the z axis uses a single axis robot type KK40 lead 1 mm which is able to lift 0.066 kg loads and move at a maximum speed of 190 mm/s as far as 30 mm. The servo motor used has a torque value of 0.48 Nm for 50 W and 0.96 Nm for 100 W.